Influência do tipo e do tempo de duração de cura nas propriedades mecânicas de concretos de alto desempenho (CAD) produzidos em períodos quente (t>25°C) e de baixa umidade relativa do ar (h<50%) - BESERRA, Simone Ataíde (2005)
In the case of conventional concrete, small constructive defects, variations of mix proportion or even inadequate curings can not compromise significantly the material. No longer HPC demands a severity in the control since its dosage until the execution, therefore any imperfection can bring serious damages to the material or the structure. Amongst the relative aspects most important to the total quality of any concrete it is the curing, that becomes basic when is about HPC. The curing of the high performance concrete constitutes in a controversial subject in the technician area as well as the type and duration of it, therefore the necessity of a deeper refined study on this subject. This research verifies the influence of the type and time of duration of curing in the mechanical properties of the HPC (compressive strength, flexion tensile strength and module of deformation), produced in Goiânia in hot period (t>25ºC) and of low relative humidity of air (h<50%) situation this considered critical for NBR 14931/2003 and predominant in the months of May the September in this region. In the experimental study were produced HPC of target compressive strength 60, 80 and 100MPa, from the Furnas Mix Proportion Method, using cement CP II-F-32, silica fume, polycarboxylate based superplasticizer, natural sand and crushed stones nº 0 of the granulite. 14 cures of different type and times of duration had been applied: curing with permanence of 1, 3, 7, 14, and 28 days inside of the humid chamber; curing with aspersion of water during 1, 3, 7, 14 and 28 days; chemical curing based on paraffin and chemical curing based on chloride rubber; cure for aspersion of water during 7 days and later sealing of the part with membrane of curing based on chloride rubber and air curing. For concretes of target compressive strength to the 28 days of 60 MPa and 80 MPa, the best type of curing was "saw humid" (curing in humid chamber and curing with aspersion of water) and the best time of duration humid was 7 days. For the one of 100 MPa the best type of curing also was "saw humid", however the duration time was 14 days. According to the chemical curing, some times the results had been even though less than to the one of reference (air curing). Among the two types of used chemical curing, difference in the results of compressive strength was not verified, despite the chemical membrane based on paraffin has an inferior cost to the chloride rubber base.